The effect of DYS-14 copy number variations on extracellular fetal DNA quantification in maternal circulation - Hromadnikova, Ilona; Benesova, Martina; Zejskova, Lenka; Stehnova, Jana; Doucha, Jindrich; Sedlacek, Petr; Dlouha, Klara; Krofta, Ladislav (DNA and cell biology, 2009)
The aims of our research involved to investigate DYS-14 copy number variations in healthy males, to quantify extracellular DNA in maternal circulation in normal versus complicated pregnancies, and to study variations in the DYS-14 copy number in extracellular male fetal DNA. Fifty-five healthy males, 43 uncomplicated male singleton pregnancies (23 sampled at the 16th week and 20 sampled at the 36th week), and 15 pregnancies with placental insufficiency (PI)-related complications (mean 34.1 weeks) were analyzed using real-time PCR with DYS-14 sequence, sex determining region Y (SRY), and beta-globin (GLO) genes used as markers. Increased levels of extracellular DNA were detected in PI-related complications relative to gestational age-matched controls (SRY, p < 0.001; DYS-14, p = 0.007; GLO, p < 0.001). When the mean + 2SD (standard deviation) of controls was used as a cutoff, SRY, DYS-14, and GLO achieved 91.7%, 68.8%, and 94.4% accuracy, respectively, for differentiation between normal and complicated pregnancies. Considerable variations in the DYS-14 copy number in healthy males (mean 52.6) and extracellular DNA were found. A lower DYS-14 copy number was observed in PI-related complications (mean 83.5) compared to uncomplicated pregnancies (16th week: mean 114.2, p = 0.02; 36th week: mean 142.8, p = 0.04). The DYS-14 copy number was higher in extracellular DNA throughout gestation relative to healthy males. We concluded that, regarding interindividual copy number variations, the DYS-14 sequence is not an optimal marker for extracellular fetal DNA quantification for differentiation between normal and complicated pregnancies.
Keywords: výsledek těhotenství; Infant; Humans; Pregnancy; Case-Control Studies; kojenec; lidé středního věku; dítě; studie případů a kontrol; Child; Prenatal Diagnosis; lidský chromozom Y; gestační stáří; Female; mladý dospělý; dospělí; genová dávka; Pregnancy Outcome; lidé; Cell Cycle Proteins; Sex-Determining Region Y Protein; Mothers; DNA; Fetus; předškolní dítě; Adult; plod; Placental Insufficiency; placentární insuficience; Gestational Age; ženské pohlaví; Male; Chromosomes, Human, Y; Middle Aged; Adolescent; těhotenství; prenatální diagnóza; protein oblasti určující pohlaví na chromozomu Y; proteiny buněčného cyklu; Young Adult; matky; mužské pohlaví; Child, Preschool; Gene Dosage; mladiství